Artificial-intelligence Based Multi-objective Optimisation for Concrete Incorporating Solid Wastes - Wang, Yufei (Curtin University, 2025)
The construction industry is a major contributor to carbon emissions and resource depletion. This thesis advances sustainable construction by integrating solid waste recycling, advanced construction materials, 3D concrete printing, machine learning, optimisation techniques, and life cycle assessment. By developing predictive models, optimisation strategies, and environmental evaluations, this research enhances material efficiency and mitigates environmental impact. The findings provide a scientific foundation for transitioning towards resilient, sustainable, and circular construction practices.